Gangguan Skizofrenia pada Tokoh Utama dalam Novel Skizofrenia Karya Disadisso : Kajian Psikologi Sastra Lev Vygotsky - Sheila Rohmatika Fitria; Ahmad Ilzamul Hikam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Mental disorders, particularly schizophrenia, are psychological phenomena that are widely addressed in literary works because they can reflect the inner conflicts of individuals as well as the social problems surrounding them. This study aims to uncover how schizophrenia is represented in the main character of the novel